Developing a multi-institutional PACS archive and designing processes to manage the shift from a film to a digital-based archive. - Laprise NK; Hanusik R; FitzGerald TJ; Rosen N; White KS (Journal of Digital Imaging, 2009)
The Quality Assurance Review Center (QARC) works to improve the standards of care in treating cancer by improving the quality of clinical trials medicine. QARC operates as a data management and review center providing quality assurance services for multiple external groups including cooperative groups and pharmaceutical companies. As the medical world migrates from analog film to digital files, QARC has developed an innovative and unique digital imaging management system to accommodate this trend. As QARC acquires electronic data from institutions across six continents, the system is continually developed to accommodate Digital Imaging and Communications in Medicine (DICOM) imaging originating from a wide variety of Picture Archival and Communications System (PACS) manufacturers, thus creating one of the largest and most diverse multiinstitutional imaging archives in the cancer research community.